Latin American Migrations to the U.S. Heartland: Changing Social Landscapes in Middle America - LINDA ALLEGRO, ANDREW GRANT WOOD (University of Illinois Press, 2013)
We began conceptualizing this project in 2007 when Oklahoma lawmakersâ€” concurrent with other legislators elsewhere in the countryâ€”passed a draconian law attempting to expunge the undocumented population from the state. As Latin Americanists educated in New York and California, we were disturbed by the many inaccuracies disseminated about immigrants, the scapegoating of people of Latin American heritage, and the countless diatribes about â€œillegalsâ€ in the media. Before long, this new wave of antiimmigrant fervor had crystallized into an angry narrative alleging an â€œunworthinessâ€â€” and possibly even criminal intentâ€”on the part of nearly all Latin American immigrants. Over and over we heard people ask: Why were they here? What public services were they taking advantage of? Why didnâ€™t they speak English? What part of illegal donâ€™t you understand? From our perspective, the prevailing public discourse that so dehumanized border crossers stood in sharp contrast to the hardworking and morally grounded individuals and families we knew. Miguel, a talented corrido songwriter from MichoacÃ¡n, worked as a landscaper tending the lawns of individuals who barely knew of his existence. As a day laborer, his full life as a musician, father, and friend remained unknown. Juanâ€™s daughter, Amanda, with undocumented status, actually supported her unemployed American husband working as a nanny. Antonia, having buried a husband and leaving seven children behind in Guatemala, followed a cousinâ€™s path to rural Oklahoma where she worked in a cafeteria kitchen and sent her paychecks home. The determined work ethic of these people, as far as we could see, ran contrary to the often prejudicial, two-dimensional portrayal of â€œHispanics.â€ Given these and many other similar situations, we felt inspired to render a more humane depiction of Latin American migrants in the U.S. Heartland.